REGINOAL PECULARITIES OF HYPOTENSIVE DRUGS USE BY PREGNANT WOMEN - N. A. Konyshko; A. V. Krikova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Hypotensive drugs applied by pregnant women in gestational and post-gravidary periods are limited by four basic groups of antihypertensive substances. Administration of other drugs is rare and do not have a tendency to grow. The majority of drugs corresponds to the following criteria: they are low cost, they are used during several decades. Beta-adrenergic blockers are the leaders among the hypotensive drugs for pregnant women. On the whole, pharmacotherapy of a high blood pressure of contingent under study corresponds to international recommendations